Quantum Dots-Based Immunochromatographic Strip for Rapid and Sensitive Detection of Acetamiprid in Agricultural Products - Liu, Ying; Zhao, Ying; Zhang, Tianyi; Chang, Yunyun; Wang, Shuangjie; Zou, Rubing; Zhu, Guonian; Shen, Lirong; Guo, Yirong (Frontiers in Chemistry, 2019)
In this study, a rapid and sensitive immunochromatographic strip (ICS) assay based on quantum dots (QDs) was developed for qualitative and quantitative detection of acetamiprid in agricultural samples. Acetamiprid-ovalbumin conjugates (ACE-OVA) and goat anti-mouse IgG were sprayed onto nitrocellulose membrane as test line and control line. Two kinds of anti-acetamiprid monoclonal antibodies (mAb) obtained in our lab were characterized by ELISA and surface plasmon resonance assay. The competitive immunoassay was established using QDs-mAb conjugate probe. The visual detection limit of acetamiprid for qualitative threshold was set as 1 ng/mL by naked eyes. In the quantitative test, the fluorescence intensity was measured by a portable strip reader and a standard curve was obtained with the linear range from 0.098 to 25 ng/mL and the half maximal inhibitory concentration of 1.12 ng/mL. The developed method showed no evident cross-reactivities with other neonicotinoid insecticides except for thiacloprid (36.68%). The accuracy and precision of the developed QDs-ICS were further evaluated. Results showed that the average recoveries are from 78.38% to 126.97% in agricultural samples. Moreover, to test blind tea samples, the QDs-ICS showed comparable reliability and high correlation with ultra-performance liquid chromatography-tandem mass spectrometry. The whole sample detection could be accomplished within 1 h. In brief, our data clearly manifested that QDs-ICS was quite qualified for rapid and sensitive screening for acetamiprid residues in agricultural products analysis, and paved the way to point-of-care testing for other analytes.